Artificial Reefs in Florida 101 – why are they built? Part 1 of an Artificial Reef series - Lisa Chong; Angela B. Collins; Holly Abeels; Anna Braswell; Andrew Ropicki; Scott Jackson; Ed Camp (EDIS)
Increasingly, coastal managers are placing artificial reefs in marine waters. These long-lasting habitat alterations have measurable effects on fish, fishers, divers, fisheries, and marine social ecological systems. Understanding how artificial reefs function is necessary to make good decisions about future artificial reefs. Scientific research on many aspects of artificial reefs is not always summarized and explained. In response to this need, we designed a 4-part series called Artificial Reefs 101. This publication, Part 1 of the Artificial Reefs 101 series, explains why artificial reefs are built. It defines what artificial reefs are and explains why people build and deploy artificial reefs. It should help the interested public understand how artificial reefs affect marine resources, and provide a background and baseline of information for decision-makers such as local officials, management agency personnel, and Extension agents.